Effect of Nesting on Extensor Motor Behaviors in Preterm Infants: A Randomized Clinical Trial - Zahra Eskandari; Naiemeh Seyedfatemi; Hamid Haghani; Amir Almasi-Hashiani; Parisa Mohagheghi (Mashhad University of Medical Sciences, 2020)
Background: The aim of this study was to investigate the effect of bedding preterm infants in nests on their motor behaviors in a neonatal intensive care unit (NICU) in Iran. Methods: In this randomized controlled trial, 44 clinically stable preterm infants, admitted to the NICU, were recruited and randomly divided into two groups of control and intervention. The routine of the unit was to take care of infants on a flat mattress. The intervention was a U-shaped cloth nest in which the intervention group was bedded for 7 days. The control group consisted of infants who were normally cared without any boundaries. All infants were videotaped before and on the last day of the intervention. The motor behaviors, as defined in the Newborn Individualized Developmental Care and Assessment Program (NIDCAP) sheet, were analyzed in each of the films. Results: To compare the number of total extensor motor behaviors between the two groups, the change score in each group was calculated and compared between the two groups. The mean change scores in the intervention and control groups were -21.36±13.5 and 2.32±7.9, respectively. Accordingly, nesting significantly reduced the occurrence of unstable behaviors in the intervention group, compared to that in the control group (P<0.001). Conclusion: According to the findings, supporting the preterm infant body even by accessible materials could enhance their neurodevelopmental strengths and motor behavior stabilities.